Analisis Komunikasi Peserta Didik Pada Pembelajaran Sejarah Masa Pandemi Covid-19 - Fathurrahman Fathurrahman; Reyhan Ainun Yafi; Rhoma Dwi Aria Yuliantri; Risky Setiawan (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2022)
In online learning, communication is an important part that must be established between teachers and students. The communication that exists in SMA Negeri 1 Rasau Jaya still has various problems such as a lack of responses from students when the teacher delivers the material. In addition, limited smartphone memory storage to download the applications used. The purpose of this study was to analyze the communication between teachers and students in online learning during the Covid-19 period in history subject learning. This research used a qualitative method with a descriptive approach. Data were collected by observation, interviews, and literature studies. Data were analyzed using the Miles and Huberman measurements. The results showed that the communication between teachers and students at SMA Negeri 1 Rasau Jaya was not optimal. This is due to the use of Edmodo which is not all students give a positive response and sometimes there is no response at all, so the learning process becomes less fun and seems boring.Keywords: communication, online learning, pandemic Covid-19